Trends and hotspots in pulmonary fibrosis biomarker research: a bibliometric analysis - Wang, Ling; Huang, Jianliang; Tan, Gan; Zhang, Yurou; Xia, Mingkai; Kang, Zhen; Xiao, Yun; Lei, Mingsheng (Frontiers in Medicine, 2025)
BackgroundPulmonary fibrosis is a fatal disease characterized by progressive scarring of lung tissue, with a complex pathogenesis and limited therapeutic options. The identification of robust biomarkers is critical for addressing key clinical challenges, including delayed diagnosis and poor prognostic assessment.MethodsThis study systematically analyzes global research trends and emerging hotspots in pulmonary fibrosis biomarkers by examining literature from 2001 to 2024 indexed in the Web of Science Core Collection. Utilizing a suite of bibliometric tools including VOSviewer, CiteSpace, Bibliometrix, Scimago Graphica, and OriginPro 2021, this work provides the first comprehensive insight into the evolving landscape of biomarker research in pulmonary fibrosis.ResultsThis study included a total of 2,519 articles and reviews related to pulmonary fibrosis biomarkers. Since 2005, publication trends in this field have steadily increased. Research on pulmonary fibrosis biomarkers has involved 71 countries, 3,036 institutions, 760 journals, and over 14,000 researchers. China produced the highest number of publications (n = 535, 21.2%, TLCS = 459), followed by the United States (n = 529, 21%, TLCS = 3,527) and Japan (n = 270, 10.7%, TLCS = 1,279), with the United States exerting the greatest influence. The UNIVERSITY OF CALIFORNIA SYSTEM (n = 164) and HARVARD UNIVERSITY (n = 141) contributed the largest bodies of work. The most prolific authors in this domain are BARGAGLI E (n = 45), MAHER TM (n = 42), and MARTINEZ FJ (n = 32). The AMERICAN JOURNAL OF RESPIRATORY AND CRITICAL CARE MEDICINE is widely regarded as the leading journal in this field. In recent years, research has increasingly focused on macrophages, computed tomography, and Muc5b promoter polymorphism, among other areas. The concept of “double blind” reflects the translational trend of biomarkers toward clinical applications, particularly their potential utility in acute exacerbations of pulmonary fibrosis, interstitial pulmonary fibrosis, cystic pulmonary fibrosis, and radiation-induced pulmonary fibrosis.ConclusionThe clinical application of gene and imaging biomarkers achieved through the integration of multiple parameters and multi-omics fusion represents a promising future trend and emerging hotspot in pulmonary fibrosis biomarker research.